Kajian Kenyamanan Termal Bale Meten Sakutus di Seminyak, Kabupaten Badung – Bali - Anak Agung Gede Raka Gunawarman; Made Suryanatha Prabawa (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2020)
Bale meten in Balinese architecture is one of the buildings in the yard of a traditional Balinese house that has a function as a place to store heirloom objects (it can also be called a sacred space) or as a place to sleep for the oldest person. The application of sakutus on the bale meten in the indoor area is a solution for the outside air gap to enter the room. Bale Meten Sakutus with Kampiah roof construction also functions as air circulation as well as the gap between the roof and the wall. The application of sustainable principles is very clearly applied to Balinese architectural buildings, both from the use of natural air and natural light. The loss of sakutus in the space in the bale meten indirectly causes changes in the circulation of air in and out. The closure of the gap between the wall and the roof due to the use of the ceiling may make air circulation not smooth anymore. The proof of the thermal comfort of an architecture that is still strong with traditional values ​​and principles is the subject of this research. The method chosen for the implementation of this research is a mixed method with a focus on site or field research. The object of research in the form of bale meten will consist of two types in the same location, if necessary, it is a house or yard that is adjacent / neighboring in order to obtain optimal and objective data. Measurements were made on the same day and hour with the help of measuring instruments and temperature data from Google at the time of data collection.